Waqf Governance, Constitutional Secularism, and Minority Rights: Assessing India’s UMEED Act 2025 in Comparative Perspective - Sirajuddin Shaikh; Siti Harizah (Asian Journal of Muslim Philanthropy and Citizen Engagement, 2026)
The waqf (Amendment) Act 2025, renamed the Unified waqf Management, Empowerment, Efficiency and Development (UMEED) Act, represents a transformative moment in India’s governance of Islamic endowments, introducing sweeping institutional changes including the abolition of waqf by user, mandatory registration, restructuring of waqf boards, and expanded executive authority. This study examines the constitutional implications of these reforms through doctrinal legal analysis and comparative examination of waqf governance in Turkey, Malaysia, and Indonesia. The findings reveal that while the UMEED Act pursues administrative modernization through transparency, accountability, and digitization, it simultaneously reconfigures the balance of power between state authority and religious autonomy, raising fundamental questions about minority rights under Articles 25–30 of the Indian Constitution. The comparative analysis demonstrates that successful waqf governance requires a hybrid model that combines regulatory efficiency with constitutional safeguards for religious freedom, judicial oversight, and community participation. The study argues that the UMEED Act constitutes a defining constitutional test of India’s commitment to secularism and minority protection, with implications for Muslim philanthropy, institutional legitimacy, and democratic governance in pluralist societies. The findings offer policy-relevant insights for strengthening waqf governance while preserving religious autonomy and minority self-governance.